ANALISIS PENGARUH CITRA GELAP TERHADAP KINERJA METODE HIGH BOOST FILTERING DAN ADAPTIVE HISTOGRAM EQUALIZATION - Muhammad Fitra Hanafiah; Rismayanti; Yessi Fitri Annisah Lubis (SNASTIKOM, 2022)
The Images taken with a digital camera at night with minimal lighting will produce a dark image and it is difficultto recognize objects in it. The image results obtained appear black and the details in the image are not clearlyvisible. In such conditions, it is necessary to improve the image (image enhancement) which aims to get the imagedisplay with a better form of visualization. This study aims to examine the effect of dark images on the performanceof the High boost Filtering method and the Adaptive Histogram Equalization method in improving image quality,especially the types of dark images taken from smartphone cameras at night so that they can provide solutions inthe form of applications and information on how to improve image quality on dark images so that detailed imageinformation can be seen visually. The test results using three dark images in bitmap format (*.bmp) taken from asmartphone camera at night with different lighting affect the performance of the High boost Filtering and AdaptiveHistogram Equalization in improving image quality, meaning that it gets darker. Image object then the result isalso not good and vice versa. The best results use the High boost Filtering method. The High boost Filteringmethods produces an image histogram that is evenly distributed so that detailed image information can be seenvisually.